1961
DOI: 10.15281/jplantres1887.74.220
|View full text |Cite
|
Sign up to set email alerts
|

On Two New Species of Spirillum

Abstract: On Two New Species of Spirillum by Yasuke TERASAKI*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…From this he concluded that the spirilla probably had not originated in the manure itself. Terasaki (175)(176)(177)(178)180) isolated many strains of aquaspirilla from freshwater shellfish but concluded that such spirilla were probably not present as normal or parasitic inhabitants of the mussels but were instead present in the adherent mud (178).…”
Section: Ecology Of Spirilla Habitat and Numbers In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…From this he concluded that the spirilla probably had not originated in the manure itself. Terasaki (175)(176)(177)(178)180) isolated many strains of aquaspirilla from freshwater shellfish but concluded that such spirilla were probably not present as normal or parasitic inhabitants of the mussels but were instead present in the adherent mud (178).…”
Section: Ecology Of Spirilla Habitat and Numbers In Naturementioning
confidence: 99%
“…In some cases enrichment cultures that allowed spirilla to reach numbers sufficiently high to warrant plating on solid media have employed enrichment media that were not di-lute. Such media are exemplified by putrid infusions of freshwater or marine shellfish (175)(176)(177)186), infusion of grass cuttings (30), algal infusions (198), or defined media (88,198). As noted by Williams and Rittenberg (198) and Jannasch (88), spirilla appear to be enriched at the surface of freshwater cultures or just beneath the surface scum that forms in marine cultures.…”
Section: Isolation Of Spirillamentioning
confidence: 99%
“…Williams and Rittenberg used morphology primarily and nutrition secondarily to divide the genus into 19 species and provided many supplementary physiological data. Since the work of Williams and Rittenberg, a number of additional species have been described (7,19,27,40,41,44). The serological relationships among spirilla, based on thermolabile antigens, have recently been investigated by McElroy and Krieg (24).…”
mentioning
confidence: 99%